2019
DOI: 10.3897/zookeys.816.29738
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic review of the pericaline ground-beetles in Taiwan, with descriptions of new species (Coleoptera, Carabidae, Lebiini)

Abstract: A taxonomic review of the known Taiwanese taxa of the pericaline Lebiini, this paper includes a key to the genera, keys to species, descriptions, and redescriptions of all species, illustrations, geographic range maps, re-rankings, and new synonymies. In total 34 species are treated, nine of which are described as new. A new genus and new species are as follows: Bellavalentisgen. n., (type species Dolichoctiskuzugamii Shibata, 1967); Amphimenesabsensacidussp. n.; Amphimenesbeichatiensissp. n.; Amphimenescarina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…4C), which mimics erotylids in coloration, its possible hosts which also occur in Gutianshan NP (cf. Erwin and Erwin 1976;Hunting and Yang 2019)), the collyridine Tricondyla macrodera (Fig. 4D), which not only resembles ants in their habitus, but also regularly hunts them (Shook and Wu 2007;own observations), and the platynine species (cf.…”
Section: Catches From Flight Interception Trapsmentioning
confidence: 97%
“…4C), which mimics erotylids in coloration, its possible hosts which also occur in Gutianshan NP (cf. Erwin and Erwin 1976;Hunting and Yang 2019)), the collyridine Tricondyla macrodera (Fig. 4D), which not only resembles ants in their habitus, but also regularly hunts them (Shook and Wu 2007;own observations), and the platynine species (cf.…”
Section: Catches From Flight Interception Trapsmentioning
confidence: 97%
“…An example is his publication about the ectoparasitoidism of Eurycoleus macularis (Chevrolat, 1835) which develops on fungus beetles of the genus Amphix ( Endomychidae ), with larvae and adults both relying on the host as prey and living together with them ( Erwin and Erwin 1976 ). More than 40 years later, Hunting and Yang (2019) reported that they found another percaline ground beetle in Taiwan, namely Lioptera erotyloides Bates, 1883, which is quite similar in coloration to fungus beetles of the subfamily Megalodacninae ( Erotylidae ). Ground beetles and fungus beetles were encountered together.…”
Section: Natural History-based Sciencementioning
confidence: 99%
“…HABITATS AND HABITS. All specimens of A. carinacaulis were hand collected in mixed forests at 640-1850 m elevations at night [Hunting, Yang, 2019].…”
Section: Diagnosis Aedeagusmentioning
confidence: 99%
“…Larger, BL 6.3-7.7 mm. -Myanmar, Thailand to Vietnam (Dong Nai, Binh Phuoc, Dak Lak, Nghe An [Habu, 1964], up to 1.42 [Hunting, Yang, 2019] Figs 6-10. Dorsal habitus: 6 -Amphimenes acutipennis sp.n., # paratype from Kon Plong District; 7 -A. basipunctatus sp.n., holotype; 8 -A. tonkinensis sp.n., holotype; 9 -A. konplongensis sp.n., holotype; 10 -A. femoralis sp.n., # paratype.…”
Section: Introductionmentioning
confidence: 99%